Cyclotrimerization of arylalkynes on au(111) - Liu, Jia; Ruffieux, Pascal; Feng, Xinliang; Muellen, Klaus; Fasel, Roman (Chemical Communications, 2014)
Surface-assisted cyclotrimerization of arylalkynes was studied on Au(111) by means of scanning tunneling microscopy (STM) under ultra-high vacuum (UHV) conditions. Upon thermal activation, cyclotrimerization of 1,3,5-tris-(4-ethynylphenyl)benzene proceeds readily and with high selectivity, and results in two-dimensional covalently bonded polyphenylene nanostructures exhibiting a honeycomb topology. © 2014 The Partner Organisations.
CRIS-Team Scopus Importer:2023-03-20